KONFLIK LAHAN PERKEBUNAN KELAPA SAWIT: KASUS PT. WANA SARI NUSANTARA (WSN) DENGAN WARGA DESA SUNGAI BULUH KECAMATAN SINGINGI HILIR KABUPATEN KUANTAN SINGINGI TAHUN 2013 - Nefi Fitriana; Raja Muhammad Amin, (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The study, entitled "Oil Palm Land Conflict: Case PT. Wana Sari Nusantara (WSN) with Villagers of Sungai Buluh District of Singingi Hilir Kuantan Singingi Regency Year 2013". Associated with the land or soil, a production source that is needed by all people, therefore many people who want to get it. It is not unusual when the soil become an arena for the struggle for the interests of the various parties are no exception PT. Wana Sari Nusantara with Villagers Sungai Buluh. Both of these parties want ownership of 905 acres of land concession of PT. Wana Sari Nusantara administered by some villagers Sungai Buluh.This research tries to study on land conflicts involving oil palm plantations, PT. Wana Sari Nusantara (WSN) with most of the villagers of Sungai Buluh in 2013 that each party has a different opinion so it is interesting to study and this is the background of this research. The formulation of the problem in this study are: 1) What are the factors causing conflicts between oil palm plantations, PT. Wana Sari Nusantara with Villagers Sungai Buluh; and 2) What is the role of Local Government in dealing with conflict resolution oil palm plantations. In addition, this study aims to determine the factors that cause some conflicts between oil palm plantations, PT. Wana Sari Nusantara with Villagers Sungai Buluh and the role of Local Government in dealing with conflict resolution oil palm plantations.The theory used in this study include the Conflict Theory, Land Rights, right to cultivate, Land Conflict, Land Policy, Government Authority, and Land Dispute Resolution. The research method used was a qualitative descriptive research. Location of the research done in PT. Wana Sari Nusantara. While informants who provide information such as Riau Forestry Service, Department of Plantation Riau, Riau Province National Land Agency, the Forest Service District Kuantan Singingi, Kuantan Singingi District Plantation Office, Singingi Kuantan district legislature, the National Land Agency Singingi Regency Kuantan, Kuantan Singingi District Police, head of government affairs districts of Singingi Hilir, the village secretary of Sungai Buluh, Party PT. Wana Sari Nusantara (WSN), the NGO Association of Indonesian Farmers Independent (AIPI), Chairman of BPD Sungai Buluh and the villagers of Sungai Buluh in conflict. The data collection was done by interview, observation, and documentation.The results of this study may show on the chronology of the conflict between the oil palm plantation, PT. Wana Sari Nusantara with the villagers of Sungai Buluh, the factorsthat led to the emergence of the conflict, the role of local government and the province ofRiau Kuantan Singingi in addressing conflict resolution, conflict resolution description, aswell as obstacles to conflict resolution. The conclusion of this study is basically a summary ofthe contents and discussion. The results of this study should be able to help provideinformation in the resolution of conflict oil palm plantations.Keywords: Conflict Farm, Right Of Tenure By Long Lease, Role of government, PT.Wana Sari Nusantara (WSN), and Villagers of Sungai Buluh.